2021
DOI: 10.1111/ijd.15887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of filaggrin loss‐of‐function variants in Chilean population with and without atopic dermatitis

Abstract: Background Filaggrin (FLG) loss-of-function variants are major genetic risk factors for atopic dermatitis (AD), but these have not been studied in Latin American populations with and without AD. Methods FLG variants R501X and 2282del4 were genotyped in 275 Chilean adults with and without AD from the "Early origins of allergy and asthma" (ARIES) cohort and in 227 patients from an AD cohort based in Santiago, Chile.Results Among adults in the ARIES cohort, 3.3% were carriers of R501X and 2.9% of 2282del4 variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A sizable number of people of European ancestry can be found in the populations of many Latin American countries. Chilean research found that 9.3 percent of their patient group had filaggrin mutations, which are commonly found in European individuals with AD [ 68 ]. Filaggrin and claudin-1, a protein involved in tight junctions, were both less abundant in the skin of Brazilian patients.…”
Section: Extra-cutaneous Clinical Manifestations Among Different Racesmentioning
confidence: 99%
“…A sizable number of people of European ancestry can be found in the populations of many Latin American countries. Chilean research found that 9.3 percent of their patient group had filaggrin mutations, which are commonly found in European individuals with AD [ 68 ]. Filaggrin and claudin-1, a protein involved in tight junctions, were both less abundant in the skin of Brazilian patients.…”
Section: Extra-cutaneous Clinical Manifestations Among Different Racesmentioning
confidence: 99%
“…The population in some of the LA countries is predominantly of European origin. A study in Chile showed that filaggrin variants commonly seen in European patients with AD were observed in 9.3% of Chilean patients [12]. There was an impaired expression of filaggrin and claudin-1 (a tight junction protein), in the skin of Brazilian patients.…”
Section: Epidemiology Of Admentioning
confidence: 99%
“…Most information comes from survey-based studies, clinical studies in specific cities, 34 , 36 , 37 and other studies reporting AD treatment outcomes that provide data on clinical characteristics in certain LA countries. 27 , 38 , 39 A recent survey of filaggrin ( FLG ) gene loss-of-function mutations in Chile found that the 2 most common FLG gene variants (R501X and 2282del4) are present in 9.3% of Chilean patients, a similar rate to the European population, 40 whereas another study on FLG -2 gene polymorphisms in Brazilian patients found no relationship with AD. 41 …”
Section: Knowledge Gaps In Ad Research In Lamentioning
confidence: 99%